Hubungan Pengetahuan, Peran Petugas Kesehatan, dan Dukungan Keluarga terhadap Perilaku Pencegahan Stunting pada Ibu Hamil di Wilayah Kerja Puskesmas Pondok Meja Jambi Tahun 2023 - Azarine, Sherin; Meinarisa, Meinarisa; Sari, Putri Irwanti (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2023)
Suffering from chronic malnutrition during early childhood leads to stunting. This study aims to investigate the correlation between pregnant women's preventive behavior and their knowledge, support from health workers, and family support in the Pondok Meja Muaro Health Center Jambi in 2023. The research utilized an associative analysis design and a cross-sectional approach. The instrument used in this study was a questionnaire by testing the validity and reliability tests. The findings indicated that the majority of pregnant women exhibited positive stunting prevention behaviors, with 39 participants falling under the